MRI Pattern of Various Cochlear Implant Electrodes In Vivo - Sudhoff, Holger; Riemann, Conrad; Gehl, Hans Björn; Todt, Ingo (Annals of Otology and Neurotology, 2019)
Introduction Recent developments regarding cochlear implant magnets (e.g., a bipolar diametral magnet) and refined surgical technique (e.g., implant positioning) have made a significant impact on the relation between a cochlear implant and magnetic resonance imaging (MRI). MRI scanning has changed from a contraindication to a diagnostic tool. For the first time, a pain-free in vivo evaluation of the cochlea’s fluid state, following the insertion of an electrode, has become possible via MRI scanning. The aim of this study was to evaluate various cochlear implant electrodes’ MRI-specific patterns.Materials and Methods In a retrospective study, we evaluated the MRI pattern of casting iron (CI) electrodes in a 3T T2 turbo spin echo (TSE) sequence after a surgery with Medel Flex 28, Flex 24, AB HFMS, and MRI at 1.5 T T2 TSE with the Oticon EVO array.Results A generally different axial MRI pattern between the “lateral wall” electrodes and the “modiolar” electrodes at the basal turn could be observed. A difference in terms of electrode length/insertion depth could not be found at the present scan resolution. Electrode contacts have an impact on the MRI signal-diminishing pattern.Conclusion At T2 sequences, an electrode design-specific MRI pattern can be observed.
Keywords: magnetic resonance imaging; cochlear implant; electrode